Speech Prosody 2020 2020
DOI: 10.21437/speechprosody.2020-93
|View full text |Cite
|
Sign up to set email alerts
|

Papuan Malay word stress reduces lexical alternatives

Abstract: This study investigates the extent to which word stress facilitates word disambiguation in Papuan Malay. Although there is consistent acoustic support for word stress patterns in this language, the function of word stress in Indonesian languages, including Papuan Malay, has been disputed in several studies. Based on a word list of phonetically transcribed Papuan Malay words, an analysis of wordembeddings was carried out. The number of words that are embedded in other words was shown to explain the role of word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This result crucially complements the lexical analysis in Kaland and van Heuven (2020) and Kaland et al (2021), in which a representative subset of the Papuan Malay lexicon showed that stress information could have a facilitating effect word disambiguation, in addition to the segmental information. Although this facilitation is smaller in Papuan Malay than in languages with less regular stress patterns such as Spanish, the results showed that the Papuan Malay lexicon leaves room for a facilitating role of stress to a similar extent as found for English (Kaland & van Heuven, 2020;Kaland et al, 2021). The results of the current study confirm that listeners are indeed able to rely on stress cues for word disambiguation.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…This result crucially complements the lexical analysis in Kaland and van Heuven (2020) and Kaland et al (2021), in which a representative subset of the Papuan Malay lexicon showed that stress information could have a facilitating effect word disambiguation, in addition to the segmental information. Although this facilitation is smaller in Papuan Malay than in languages with less regular stress patterns such as Spanish, the results showed that the Papuan Malay lexicon leaves room for a facilitating role of stress to a similar extent as found for English (Kaland & van Heuven, 2020;Kaland et al, 2021). The results of the current study confirm that listeners are indeed able to rely on stress cues for word disambiguation.…”
Section: Discussionsupporting
confidence: 73%
“…On the basis of the current gating experiment it can therefore be concluded that Papuan Malay listeners are indeed able to use these cues when they don't have an alternative. Given that there is a role for Papuan Malay word stress parameters to disambiguate embedded words (Kaland & van Heuven, 2020;Kaland et al, 2021), listeners have an incentive to use them and, given the current results, will do so. It should be noted that word disambiguation does not concern a problem Papuan Malay listeners face regularly.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations